Emergence of multidrug-resistant Providencia rettgeri isolates co-producing NDM-1 carbapenemase and PER-1 extended-spectrum β-lactamase causing a first outbreak in Korea - Shin, Saeam (Ann Clin Microbiol Antimicrob, 2018)
BACKGROUND: Nosocomial outbreak due to carbapenem-resistant Enterobacteriaceae has become serious challenge to patient treatment and infection control. We describe an outbreak due to a multidrug-resistant Providencia rettgeri from January 2016 to January 2017 at a University Hospital in Seoul, Korea. METHODS: A total of eight non-duplicate P. rettgeri isolates were discovered from urine samples from eight patients having a urinary catheter and admitted in a surgical intensive care unit. The β-lactamase genes were identified using polymerase chain reaction and direct sequencing, and strain typing was done with pulsed-field gel electrophoresis (PFGE). RESULTS: All isolates showed high-level resistance to extended-spectrum cephalosporins, aztreonam, meropenem, ertapenem, ciprofloxacin, and amikacin. They harbored the bla(NDM-1) carbapenemase and the bla(PER-1) type extended-spectrum β-lactamases genes. PFGE revealed that all isolates from eight patients were closely related strains. CONCLUSIONS: The 13-month outbreak ended following reinforcement of infection control measures, including contact isolation precautions and environmental disinfection. This is the first report of an outbreak of a P. rettgeri clinical isolates co-producing NDM-1 and PER-1 β-lactamase.